Stepwise pyrolysis of the kerogen from the Huadian oil shale, NE China: Algaenan-derived hydrocarbons and mid-chain ketones. (January 2016) - Zhang, Zhirong; Volkman, John K.; Xie, Xiaomin; Snowdon, Lloyd R.
Highlights: C27 –C37 mid-chain ketones found in pyrolysates of Huadian oil shale kerogen. They showed no odd/even predominance and a sharp maximum at n -C35. Predominance of alkan-ω24-ones suggests position of algaenan ether linkages. The distribution is different from pyrolysates of algaenans from Botryococcus . Stepwise pyrolysis allows fine tuning for identifying different compound types. Abstract: Kerogen from the organic rich Eocene Huadian oil shale in NE China was subjected to sequential stepwise pyrolysis at 50 °C intervals from 310 °C to 610 °C. This allowed generation of compounds according to the strength of the bonds linking them to the kerogen and thus permitted identification of compounds that were only minor constituents of one step flash pyrolysis at high temperatures such as Curie point 610 °C. Pyrolysis at 310 °C and 360 °C yielded very small amounts of n -alkanes having a distribution similar to that of the extractable hydrocarbons, which were presumed to be occluded within the kerogen since pyrolytic products such as n -alkenes were only minor constituents. Also present was the C18 isoprenoid ketone (6, 10, 14-trimethylpentadecane-2-one). The pyrolyzate at 410 °C showed a full suite of n -alkanes with a small amount of the corresponding n -alkenes, indicating that some cleavage of alkyl chains from the kerogen matrix had occurred. These showed a very low odd/even predominance apart from local maxima at n -C23 and n -C27 . The major component was prist-1-ene, which co-occurred with a small amount of the later eluting prist-2-ene. We speculate that the pristenes were generated from tocopherols (or their oxidized products) bound to the kerogen by single, easily cleaved, CO bonds. C15 –C20 isoprenoid alkanes were also observed and these might derive in part from breakdown of the isoprenoid-based algaenan produced by Botryococcus race L. The 460 °C pyrolyzate contained a dominant series of n -alkene/ n -alkane pairs as well as a series of novel long chain C30 –C37 mid-chain ketones showing no odd/even predominance. The C35 ketone was most abundant, with only traces of higher homologues. Mass spectra showed only minor amounts of fragments due to different positions of the carbonyl group and the major isomer in all cases was assigned as the alkan-ω24-one. It seems likely that these ketones are derived from pyrolysis of algaenan that had been incorporated into the kerogen, although no previous reports have identified this chain length range or position of the carbonyl group. Some similarities with the pyrolysis products of algaenan derived from eustigmatophytes were noted. In addition, a series of n -alkan-2-ones were present, which also likely result from pyrolytic breakdown of algaenan. At pyrolysis temperatures of 510 °C and 560 °C, the pyrolyzates were dominated by n -alkene/ n -alkane pairs with a greater proportion of alkenes and short chain hydrocarbons at the higher temperature. Only very small quantities of hydrocarbons were liberated at 610 °C, indicating that lower pyrolysis temperatures can be used to study immature kerogens. Our results demonstrate that stepwise pyrolysis can be a useful means for studying components of kerogens that differ in bond strength and for elucidating specific substructures related to algaenan. The data confirm that preservation of algaenan in the Huadian oil shale is a key factor in explaining its high organic content.